Grievance formation, rights and remedies : involuntary sterilization and castration in the Nordics, 1930s-2020s / Daniela Alaattinoğlu, University of Turku. - Alaattinoglu, Daniela (Law in context., 2023)
In the last century, the treatment of victims of involuntary sterilisation and castration in Nordic countries has varied drastically from state-to-state, across time and victim groups. Considering why this is the case, Daniela Alaattino♯Ÿlu investigates how laws and practices of involuntary, surgical sterilisation and castration have been established, abolished and remedied in three Nordic states: Sweden, Norway and Finland. Employing a vast range of primary and secondary sources, Alaattino♯Ÿlu traces the national and international developments of the last 100 years. Developing the concept of grievance formation, the book explores why some states have claimed public responsibility while others have not, and why some victim groups have mobilised while others have remained silent. Through this pioneering analysis, Alaattino♯Ÿlu illuminates issues of human and constitutional rights, the evolution of the welfare state and state responsibility in both a national and global context.